2012
DOI: 10.1186/1471-2334-12-369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the BACTEC MGIT 960 system and the agar proportion method for susceptibility testing of multidrug resistant tuberculosis strains in a high burden setting of South Africa

Abstract: BackgroundThe increasing problem of multi-drug-resistant (MDR) tuberculosis (TB) [ie resistant to at least isoniazid (INH) and rifampicin (RIF)] is becoming a global problem. Successful treatment outcome for MDR-TB depends on reliable and accurate drug susceptibility testing of first-line and second-line anti-TB drugs.MethodConsecutive M. tuberculosis isolates identified as MDR-TB during August 2007 to January 2008 using the BACTEC MGIT 960 systems and the agar proportion method were included in this study. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
9
3
4
Order By: Relevance
“…Zhao et al [13] studied 321 isolates (sensitivity 100% and specificity 98.6%) and Kim et al [14] studied 193 clinical isolates (sensitivity 100%, specificity 95%) using the BACTEC MGIT 960 SL DST, and their results were consistent with our results. However, Said et al [15] evaluated 343 isolates using the BACTEC MGIT 960 method and reported sensitivity of 27%, which was considerably lower than that in our study. We believe that this discordance occurred because Said et al [15] used a KAN concentration higher (5 µg/ mL) than the concentration recommended by CLSI and WHO (2.5 µg/mL) [7,8].…”
Section: Discussioncontrasting
confidence: 50%
“…Zhao et al [13] studied 321 isolates (sensitivity 100% and specificity 98.6%) and Kim et al [14] studied 193 clinical isolates (sensitivity 100%, specificity 95%) using the BACTEC MGIT 960 SL DST, and their results were consistent with our results. However, Said et al [15] evaluated 343 isolates using the BACTEC MGIT 960 method and reported sensitivity of 27%, which was considerably lower than that in our study. We believe that this discordance occurred because Said et al [15] used a KAN concentration higher (5 µg/ mL) than the concentration recommended by CLSI and WHO (2.5 µg/mL) [7,8].…”
Section: Discussioncontrasting
confidence: 50%
“…También existen métodos comerciales más rápidos como el BACTEC ™ 460TB (16), el BACTEC ™ MGIT (17), los cuales se basan en el crecimiento bacteriano en presencia del antibiótico, y los métodos genotípicos como el INNOLipa ™ _Rif.TB (Inmunogenetics) (18), el Geno Type ™ MTBDR (Hain Lifescience, Nehren, Germany) (19) y el Xpert ™ MTB/RIF (Cepheid) (20), que evalúan la resistencia por medio de la detección de mutaciones cromosómicas, y que, a pesar de ser rápidos, requieren personal entrenado, infraestructura adecuada, reactivos y equipos sofisticados y costosos, lo que hace difícil su uso en países de recursos limitados como el nuestro (21).…”
unclassified
“…The highest resistance rate was detected in isolates sent from Bursa province (located in northwestern Turkey). In the same study, MDR-TB rates (18.8% and 10.6%, respectively) 16.7% and 11.7% for SM and 6.7% and 8.3% for EMB by MOP and MGIT, respectively. The MDR-TB rates detected in our study were 10% (6 strains) using MOP and 8.3% (5 strains) using MGIT.…”
Section: Discussionmentioning
confidence: 89%
“…By adding M. tuberculosis suspension to a drug-containing MGIT tubes, an anti-mycobacterial susceptibility test (AST) can be [15] found a better correlation between MGIT and MOP on LJ medium. Said et al [16] reported that the MGIT 960 system performed well for SM and EMB when compared to MOP (sensitivity in detecting resistance 95% and 92%, respectively). Safwat et al [11] reported that the total efficiency of MGIT was 82% for susceptibility testing to SM, while it was 96% for INH, 90% for RIF and 80% for EMB.…”
Section: Discussionmentioning
confidence: 99%